Interleukin 12 at the site of disease in tuberculosis. - Zhang, M (1994)
Interleukin 12 (IL-12), a heterodimeric cytokine composed of p40 and p35 chains, has potent immunologic effects in vitro. We used tuberculous pleuritis as a model to study the immunoregulatory potential of IL-12 in vivo at the site of human infectious disease. Messenger RNAs for p40 and p35 were detected in pleural fluid from six of six patients by reverse-transcription polymerase chain reaction. By using an ELISA that detected both free p40 and heterodimeric IL-12, we found that mean concentrations were 585 +/- 89 pg/ml in pleural fluid of patients with tuberculous pleuritis, which were significantly higher than those in serum of the same patients (54 +/- 36 pg/ml), or in malignant pleural effusions (123 +/- 35 pg/ml). By using an ELISA specific for heterodimeric IL-12, we found that mean concentrations in pleural fluid of patients with tuberculous pleuritis were 165 +/- 28 pg/ml and undetectable in serum of the same patients, or in malignant pleural effusions. Bioactive IL-12 was detectable in five of five supernatants of pleural fluid cells stimulated with Mycobacterium tuberculosis. Addition of anti-IL-12 antibodies suppressed proliferative responses of pleural fluid cells to M. tuberculosis by 36 +/- 7%. These data indicate that IL-12 may play a role in the human immune response to infectious agents in vivo. We hypothesize that IL-12 contributes to the antimycobacterial immune response by enhancing production of interferon-gamma, facilitating development of Th1 cells and augmenting cytotoxicity of antigen-specific T cells and natural killer cells.